Mosques and medresses in western and eastern Kazakhstan (the late of 1990th – the early of 2000th years) - Mustafina, R. M. (Journal of Oriental Studies, 2016)
The religious life in the Western and the Eastern Kazakhstan became more active that period. There were opened a lot of mosques and medresses in thе region. Everyone had the opportunity to perfect religious knowledge. The Turkic theologies worked as missionaries and lecturers at Kazakhstan medresses and mosques according the international agreement. The young believers were the most religious active in comparative with the other groups of the population. The ethnographic research revealed that there were discussions, concerning the process of purifying Islam of alien elements and understanding of traditional Islam which demonstrated the loyality towards the Kazakh tradition of veneration of saints.